2013
DOI: 10.1038/mt.2013.17
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Metastatic Renal Cell Carcinoma With CAIX CAR-engineered T cells: Clinical Evaluation and Management of On-target Toxicity

Abstract: Autologous T cells genetically modified to express a chimeric antibody receptor (CAR) against carboxy-anhydrase-IX (CAIX) were administered to 12 patients with CAIX-expressing metastatic renal cell carcinoma (RCC). Patients were treated in three cohorts with a maximum of 10 infusions of a total of 0.2 to 2.1 × 10(9) CAR T cells. CTC grade 2-4 liver enzyme disturbances occurred at the lowest CAR T cell doses, necessitating cessation of treatment in four out of eight patients in cohorts 1 and 2. Examination of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
462
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 602 publications
(475 citation statements)
references
References 48 publications
4
462
0
2
Order By: Relevance
“…However, in other settings, CART-based targeting of antigens expressed at low levels by normal tissues has led to significant toxicities. 18,19 The paucity of well-characterized, truly tumor-specific surface antigens in AML has necessitated consideration of CART tumor-targeting strategies that may also affect normal tissues, such as bone marrow. CD123, the transmembrane a chain of the interleukin-3 receptor, is expressed on the majority of AML blasts, [20][21][22] but it is also expressed on many normal hematopoietic cells, where it is involved in hematopoietic differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…However, in other settings, CART-based targeting of antigens expressed at low levels by normal tissues has led to significant toxicities. 18,19 The paucity of well-characterized, truly tumor-specific surface antigens in AML has necessitated consideration of CART tumor-targeting strategies that may also affect normal tissues, such as bone marrow. CD123, the transmembrane a chain of the interleukin-3 receptor, is expressed on the majority of AML blasts, [20][21][22] but it is also expressed on many normal hematopoietic cells, where it is involved in hematopoietic differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…This activity has been described as the "ontarget/off-tumor" effect. Indeed, CAR T-cell therapy targeting ERBB2 and CAIX reportedly has involved lethal toxic accidents in clinical trials that were due to cytokine release syndrome triggered by the off-target recognition of low amounts of antigen (13)(14)(15)(16)(17). Clinical trials of CD19CAR T-cell therapy also revealed toxicities such as hypogammaglobulinemia, due to B-cell aplasia (18).…”
Section: Introductionmentioning
confidence: 99%
“…Three of 11 patients with active neuroblastoma achieved CR (21,22). CARs have also been developed that recognize many other targets, including HER2 for colorectal cancer (23), folate receptor-a for ovarian cancer (24), and carbonic anhydrase IX (CAIX) for renal cell carcinoma (25), but failed to show significant antitumor effect. CARs to a multitude of different antigens are currently under development.…”
Section: Tcr T Cells Tcr T Cells Are T Cells Cloned With Tcrs In Whichmentioning
confidence: 99%
“…CAIX is strongly expressed in RCC but is also present in normal tissues including liver (biliary epithelium), small intestine, and gastric mucosa. These patients experienced liver toxicity and no tumor regression (25). CARs have also been developed against HER2, an EGF receptor family member overexpressed in common malignancies including subsets of breast, colon, ovarian, gastric, and kidney cancers and melanoma.…”
Section: Tcr T Cells Some On-target Toxicities Have Been Observed Wimentioning
confidence: 99%